PERLAKUAN AKUNTANSI PEMBIAYAAN AKAD MURABAHAH PADA BMT DANA SYARIAH BERDASARKAN PSAK 102 - Tyas, Luluk Ayuning; Azizah, Rina Resiti Nur; Utami, Rida Dian; Dwijayanti, Nindy; Puspitasari, Maya Dwi (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2024)
Murabahah is one type of contract in Islam which is currently the most widely used by Islamic Financial Institutions with Islamic financing schemes. The purpose of this research is to find out how the implementation of murabahah financing is applied to BMT Dana Syariah Pedan, Klaten, Central Java and the accounting treatment of murabahah contracts based on PSAK 102. This research was conducted in Keden Village, Pedan District, Klaten Regency, Central Java. The research method used in this study is empirical juridical, which is an approach by examining primary data in the field. Then the source of the material used by collecting data through observation, interviews, and literature studies. The data analysis technique uses descriptive qualitative analysis. The results of this study indicate that the implementation of murabahah financing at BMT Dana Sayraih Pedan, Klaten must be flexible and prudent with the 5C (character, capital, capacity, collateral, and economic condition) assessment of members who apply for financing, in addition to the accounting treatment of murabahah contracts in BMT Dana Syariah it complies with PSAK 102, because the parties bound by the contract have stated the profit margin and cost of goods at the time the contract took place. Suggestions for further research are to carry out a comparative analysis using several research objects, so that it is expected to obtain balanced results regarding the treatment of murabahah accounting in several Islamic Financial Institutions.